LEGAL ASSISTANCE BY LBH IN CRIMINAL PROCEEDINGS: NORMATIVE MANDATES AND OPERATIONAL CONSTRAINTS - Saktiawan, Pratolo; Saputra, Rio; Waskito, Sarwo; Khayru, Rafadi Khan; Hardyansah, Rommy (Gapenas Publisher, 2025)
This literature study examines the effectiveness of Legal Aid Institutions (LBH) in providing legal assistance from the investigation phase to trial in Indonesia's criminal justice process. Employing a normative-analytical method, the research analyzes primary legal frameworks, including the Criminal Procedure Code (KUHAP) and the Legal Aid Law. The findings indicate that LBH possess a strong legal mandate to act as guardians of suspect/defendant procedural rights and as overseers of due process. Their effectiveness is evident in preventing procedural violations, filing pre-trial motions, and ensuring a balanced defense in court. However, this operational effectiveness is significantly constrained by profound structural and financial challenges. Chronic underfunding, disproportionate caseloads, reliance on unstable external grants, and a shortage of qualified legal personnel severely limit LBH capacity. These constraints lead to fragmented assistance, high staff turnover, and an inability to engage in strategic litigation. Furthermore, institutional resistance from law enforcement agencies, despite clear legal provisions, creates an adversarial environment that drains LBH resources. The study concludes that while the normative foundation for effective legal aid is robust, its realization is fundamentally hampered by systemic resource deficiencies and operational hurdles. The gap between law and practice underscores the need for sustainable funding models, enhanced institutional capacity, and improved synergy between LBH and state apparatus to truly actualize the right to legal counsel as a pillar of a fair trial.